EXPANSION STRATEGIES TO ACHIEVE COMPETITIVENESS - Yajid, Mohd Shukri Ab; Shukri, Shakeerah Mohd; Khatibi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
The aim of this study is to examine the strategies that are adopted by the airlines in the Malaysian territory. Air Asia was incorporated as a private limited company in Malaysia in 1993 and became Malaysia’s second national carrier in 1996 and officially commenced operations as a full-service domestic airline with only two aircrafts. The company was facing losses most of the time and eventually on December 8, 2001 the company was taken over by Datuk Tony Fernandez, a visionary leader who has no related experience in airline at all. He changed the business model and re-launched Air Asia as a low-cost carrier. Air Asia became the first low-cost carrier to take to the skies in the region. Since the takeover in 2001 with only 2 aircrafts, Air Asia has revolutionized air travel in the region to become a leading low fare airline in South East Asia. It has achieved remarkable growth in all aspects of its business such as fleet grown to 28 now, recorded strong revenue growth from good passenger seat sales, as well as achieved strong profit growth and financial position. This case study would attempt to look at Air Asia’s key success factors and challenges faced and to propose suitable strategies for Air Asia to maintain its dominance. Some of tools employed include Ratio Analysis, PEST Analysis, Porter’s 5 Forces, Competitive Profile Matrix (CPM), SWOT Analysis, Internal/External Factor Evaluation Matrix, Stakeholders’ Analysis, BCG Matrix and TOWS Matrix.